Dynamics of stock markets interdependence in the pre-and post global financial crisis period: evidence from Toda-Yamamoto causality test - Yola, Abdul-Nasir; Mohd Khan, Shazida Jan; Hidthir, Mohamad Helmi (Stock markets, interdependence, causality, Toda-Yamamoto, 2018)
This paper analysed the causal relationship between the three largest African stock markets; Nigeria, South-Africa and Egypt. The analysis was conducted for two sample periods using the index of the stock markets. The pre-crisis period between January 2000-April 2008, and the crisis/post-crisis period between May 2008-December 2016. The study employed Toda and Yamamoto robust causality test. The result from the study found evidence of no causal relationship between the three selected stock markets in the pre-crisis period. In the crisis/post-crisis period, we found a unidirectional causality from South-Africa to Nigeria stock markets. Beside this, there is no evidence of causal relationship between the stock exchange markets. Therefore, the study concluded that there is no strong difference between the causal relationship in the two analysed periods which signifies benefits of diversification between the three stock exchange markets.